Settlement of International Disputes by Peaceful Means - Faisal Abdullah, Assist. Lect. Israa (Basra studies journal, 2025)
This research addresses the settlement of international disputes by peaceful means. The devastations, tragedies, and suffering caused by wars over generations whether through the loss of human lives or the destruction of civilization have prompted jurists, politicians, and all those concerned with international affairs to seek methods to end such wars and prevent the international disputes that arise from them. International disputes are understood as contradictory claims between two or more international legal persons, the resolution of which must be carried out in accordance with the rules of international law governing dispute settlement. For a dispute to be considered international, it must involve international legal persons; however, the disputing parties do not need to be of the same nature. Thus, a dispute may arise between two states, between a state and an international organization, or even between two international organizations. The peaceful settlement of international disputes holds clear importance for the international community, as it contributes to strengthening social, political, and economic relations. Conversely, failure to settle international disputes by peaceful means, and the persistence of international conflicts and disagreements, leads to tensions in international relations and may escalate disputes and wars, making the use of force inevitable.